Efeitos do uso de aplicativos de exercícios para smartphones com supervisão presencial e a distância na capacidade funcional de idosos - Kunitake, André Issao (2022)
Background: One of the main problems that affect the older population is the loss of functional capacity, resulting from the loss of muscle strength and postural control, making the older people more fragile and dependent to perform activities of daily living. Faced with this problem, the use of mobile exercise applications aimed at older adults has been studied, however, the effectiveness of this instrument for the older adults are not clear. Objective: To evaluate the functional capacity, muscle strength, and postural balance of older adults after physical training using a smartphone physical exercise application with face-to-face and remote therapeutic supervision. Methods: Thirty-four older people participated in the study and were randomized to two training groups with an exercise application: control group - CG (face-to-face guidance), and experimental group -EG (remote guidance). The exercises were performed three times a week for 8 consecutive weeks, totaling 24 sessions. The EG performed the exercises at their homes, being monitored weekly by the therapist through telephone contact, the CG performed the exercises in the laboratory in the presence of the therapist. Study outcomes were assessed pre-intervention, after 4 weeks (1 month), and after 8 weeks (2 months). Functional capacity was measured by the ADL-Glittre Test (seconds), postural balance by the “Mini Balance Evaluation Systems Test” (score), and lower limb strength by the stand-up test (seconds). Results: There was an improvement in functional capacity (p=0.01) and postural balance (p=0.01) for both groups after one and two months, with no difference between them (p>0.05). Lower limb strength improved for both groups after two months (p=0.01), being significantly higher for the CG (p=0.04). Conclusion: This study concluded that an exercise program carried out with an exercise application on smartphones oriented in person or remotely was effective in improving functional capacity, postural balance, and lower limb strength in the older people.